Tropically adapted passive building: The impact of building design and double glazing on ambient temperature and windows' inner surface temperature - Wagner K.; Salleh S.F.; Ayodele B.V. (IEOM Society, 2023)
The high energy consumptions in buildings has been reported as one of the key contributors to global warming since the energy is mostly generated from fossil sources which is responsible for large emission of carbon dioxide. Hence, there has been series of awareness on the need for an energy efficient building that can drastically reduce energy consumption. In this study, the performance of a tropically adapted passive building (PB) was investigated in real hot tropical climate of Malaysia. Two mock-up buildings were built to represent a green, made of clay brick double-glazed PB and a conventional, made of concrete red building (RB). The ambient temperature of PB was found to be always lower than RB throughout the 7-days experiment during typical sunny/cloudy weather constellations. Besides that, the double-glazed windows installed in PB could better withstand the radiation effect of the sunlight hence maintain a much lower window IST than the single-glazed windows in RB. The average ambient temperatures of PB and RB are 29.9 oC and 31.6 oC respectively while the average window ISTs of PB and RB are 31.6 oC and 33.8 oC respectively. The study concludes that PB provides a better protection against thermal discomfort and the window is one of the critical contributors that affect ambient temperature in a warm tropical climate. IEOM Society International.